DOES ESG PERFORMANCE REDUCE CORPORATE CASH HOLDINGS? EVIDENCE FROM PANEL FIXED EFFECTS MODELS - An Nissa Regita Febriana; Evi Gantyowati (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study investigates the impact of Environmental, Social, and Governance (ESG) performance on corporate cash holding policies in an emerging market setting. Using panel data from 833 non-financial firms listed in Indonesia over the period 2021–2024 (3,327 firm-year observations), this research applies panel fixed effects estimation following Chow, LM, and Hausman tests. The results reveal that ESG performance is negatively and significantly associated with corporate cash holdings. The findings suggest that firms with stronger ESG performance tend to hold lower levels of cash, supporting the agency theory argument that ESG acts as an external governance mechanism that constrains managerial discretion and reduces excess liquidity accumulation. The study contributes to the literature by providing emerging market evidence and highlighting ESG as a determinant of corporate liquidity policy. The results are robust after controlling for firm size, leverage, tax aggressiveness, and profitability.